Ultrassonografia intraparto na predição do modo de nascimento: via, duração da segunda fase e desprendimento - Carvalho Neto, Raimundo Homero (2018)
Nowadays, the digital examination is a fundamental piece to evaluate the labor progress. However, many studies indicate a limited, subjective and low accurate method. The ultrasonography, on the other hand, being a painless and easily found method, has good reproducibility and fast learning curve. It has been routinely applied to labor phenomena studies, being named as Intrapartum Ultrasound (ITU), an efficient method to assess the cervical dilatation, progress and rotation of fetal head, being an additional tool for the clinical exam. This research consisted in a cross-sectional study, held between February and September 2017, in Maternidade Escola Assis Chateaubriand. 221 parturients with single pregnancy and > 37 weeks with cephalic fetuses, were observed. Three ultrasonographic parameters were evaluated in the first two labor phases: Pubic Arch Angle (PAA); Angle of Progression (A0P) and Head-Perineum Distance (HPD). The research aimed to diffuse the use of ITU and investigate the capacity of PAA, AoP and HPD in predicting mode of delivery, labor length of time and fetal occiput position at delivery. For analysis purposes, the mode of delivery outcomes were divided in two groups: Spontaneous Vaginal Delivery and surgical (forceps and cesarean). There was no statistical significance from PAA relating to the mode of delivery (102,6 ± 7.2 vs 100,8 ± 7,90; p=0,105). The AoP demonstrated statistical significance related to the mode of delivery, in the first and second labor phases (107,8 ± 12,10 vs 100,8 ± 13,70; p = 0,017) and (135,1 ± 119,90 vs 119,1 ± 12,10; p=0,006), being more extended in patients who presented Spontaneous Vaginal Delivery. HPD demonstrated statistical significance to the mode of delivery, on the second phase (3,42 ± 0,84cm vs 4,17 ± 0,54 cm; p=0,003), being shortened in patients who presented Spontaneous Vaginal Delivery. It was observed a more narrowed PAA, in a group of patients who presented fetus in occipito-posterior positions at delivery, when compared to a group that presented fetus in occipito-anterior positions (97,9 ± 9,60 vs 102,6 ± 7,30; p=0,049). AAP revealed itself as a variable for protection to occurrences of fetal occiput position at delivery, in occipito-posterior positions (OR= 0,9; 95% IC 0,82-0,99, p=0,026). It was observed, also, an inverse association between AoP and length of labour second phase (p=0,016), as well as a direct relation between HPD and length of labour second phase (p=0,010). It was concluded that ITU is an useful tool for studying labor progression. AoP and HPD are associated with mode of delivery and second phase length. PAA did not predict the mode of delivery, although indicated association with a persistence of posterior occipital positions at delivery.